PRELIMINARY REVISIONS OF SOME GENERA OF MALAYSIAN PAPILIONACEAE I - MEEUWEN, M. S. VAN; NOOTEBOOM, H. P.; STEENIS, C.G.G.J VAN (REINWARDTIA, 1961)
The revisions have been performed by Miss M. S. van Meeuwen (Pycnospora, Smithia, Uraria), H. P. Nooteboom (Galactia, Moghania, Rhynehosia, Stylosanthes, Zornia), and C. G. G. J. van Steenis (Cyclocarpa, Neocollettia).